2014
DOI: 10.1016/j.foodchem.2013.11.164
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent response of nitrogen stable isotope ratio to proportion of legumes in diet to authenticate lamb meat produced from legume-rich diets

Abstract: This study investigated the dose-dependent response in lamb meat of stable nitrogen isotope ratio to the dietary proportion of legumes, and the ability of the nitrogen isotope signature of the meat to authenticate meat produced from legume-rich diets. Four groups of nine male Romane lambs grazing a cocksfoot pasture were supplemented with different levels of fresh alfalfa forage to obtain four dietary proportions of alfalfa (0%, 25%, 50% and 75%) for 98 days on average before slaughter (groups L0, L25, L50 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Herbivore hair δ 15 N composition has previously been shown to be correlated with the nature and balance of N inputs and outputs in pastures, especially fertiliser type and use . The presence of legumes in pasture can also be a significant factor, as this plant group has considerably lower δ 15 N values than grasses (summer range –0.5 to 1‰ vs 5.5 to 7.5‰ in SE) and the presence of legumes has also been shown to reduce δ 15 N values in non‐N 2 ‐fixing species growing in the same soil (0–6‰ vs 2–8‰ in southern Germany) . Legumes are an important component of natural and managed pasture species mixtures across the Nordic area .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivore hair δ 15 N composition has previously been shown to be correlated with the nature and balance of N inputs and outputs in pastures, especially fertiliser type and use . The presence of legumes in pasture can also be a significant factor, as this plant group has considerably lower δ 15 N values than grasses (summer range –0.5 to 1‰ vs 5.5 to 7.5‰ in SE) and the presence of legumes has also been shown to reduce δ 15 N values in non‐N 2 ‐fixing species growing in the same soil (0–6‰ vs 2–8‰ in southern Germany) . Legumes are an important component of natural and managed pasture species mixtures across the Nordic area .…”
Section: Resultsmentioning
confidence: 99%
“…Salinity can markedly increase δ 15 N values in plants in salt marshes, due either to the input of marine nitrogen, pH changes in saline soil or salt stress affecting plant metabolism, and these changes can be passed on to herbivores grazing on these plant communities . Similarly, the proportion of leguminous plants in herbivore diet is inversely related to consumer tissue δ 15 N values, as these plants have δ 15 N values close to that of atmospheric N . Moreover, the isotopic offset between consumer and diet tissues (trophic shift) is also affected by the quantity of protein in the diet, so that herbivores consuming higher protein diets have higher diet/tissue δ 15 N differences …”
Section: Geographical Isotopic Gradients In Animal Proteinsmentioning
confidence: 99%
“…Another contributor towards 15 N-enrichment could also be the prevalence of CAM plants, as Codron et al (2005a) observed the highest d 15 N values for succulents. Conversely Devincenzi et al (2014) found that d 15 N decreased linearly with the proportion of legume in the diet of lambs. This is likely the reason for the decrease in d 15 N values for KV (9.5 ± 0.26‰) ( Table 2).…”
Section: Variability Of Meat Stable Isotope Ratiosmentioning
confidence: 85%
“…Nitrogen isotopes also provide some information about the animal's diet as the consumption of leguminous plants may decrease the d 15 N values, while the application of organic fertilisers, domestic grazing and cultivation may result in an increase of d 15 N values (DeNiro & Epstein, 1981;Devincenzi, Delfosse, Andueza, Nabinger, & Prache, 2014;Perini, Camin, Bontempo, Rossmann, & Piasentier, 2009;Piasentier et al, 2003;Sandberg et al, 2012). Not all leguminous plants may result in low d 15 N values, since Senegalia nigrescens and Colophospermum mopane (common leguminous tree taxa of the savanna) have high d 15 N values (Codron, Codron, Lee-Thorp, Sponheimer, & De Ruiter, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…The high proportion of the leguminous plants ( Fabaceae ) in the herbage and hay used in the Nebrodi farm could have affected the feed and cheese δ 15 N values. Indeed, Devincenzi et al . observed lower δ 15 N values (0.7‰ vs 3.3‰) in alfalfa than in cocksfoot herbage and a linear decrease in meat δ 15 N values related to the dietary proportion of alfalfa.…”
Section: Discussionmentioning
confidence: 99%